Healing of keyhole porosity by means of defocused laser beam remelting : Operando observation by X-ray imaging and acoustic emission-based detection - de Formanoir, Charlotte (Elsevier, 2025)
One of the remaining challenges in Laser Powder Bed Fusion (LPBF) of metals is the control of the formation of keyhole pores, resulting from a local excessive energy input during processing. Such defects can lead to degraded mechanical properties and are typically detected and/or removed after the process through non-destructive quality-inspection procedures and porosity-removal treatments. Monitoring and controlling the formation of defects during the LPBF process can allow circumventing such time-consuming and costly post-process stages. This paper develops a new approach to perform in-situ healing of deep keyhole pores, using a positively defocused laser beam with finely tuned laser remelting process parameters. Synchrotron radiographic images of the process zone are acquired during laser remelting. The use of operando imaging enables the visualization of pore removal during processing, and unveils the effect of various remelting conditions on the healing efficiency. The acoustic signals generated during laser remelting are recorded using a high-sensitivity optical microphone, and analyzed in parallel with the X-ray images, allowing the acoustic signature of defect healing to be identified. The present paper demonstrates for the first time that an airborne acoustic sensor can be used to monitor the healing of keyhole pores during LPBF.